2022
DOI: 10.3389/fped.2022.824959
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Vitamin D Level and Platelet Parameters in Children With Viral Respiratory Infections

Abstract: Apart from their classical roles, both platelets and vitamin D play important roles in inflammation and infectious diseases. This study evaluated the platelet response to viral respiratory tract infection in children aged 4–16 years, 32 with influenza, 27 with non-influenza viral infection tested by nasopharyngeal swab and 21 healthy children of the same age. Blood count, including platelet count (PLT), mean platelet volume (MPV) and other platelet indices, erythrocyte sedimentation rate (ESR), C-reactive prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Also, the median vit D level was higher in the children with a single episode of wheezing than in the control group. This could be explained by the fact that the control group consisted of older children, and in winter the serum level of vit D is reported to be lower in older children [35], as confirmed by the authors in previous studies [36,37]. In our study, significantly lower levels of vit D were found in children with recurrent wheezing than in either of those with a single episode, or in the control group, only at baseline evaluation.…”
Section: Discussionsupporting
confidence: 89%
“…Also, the median vit D level was higher in the children with a single episode of wheezing than in the control group. This could be explained by the fact that the control group consisted of older children, and in winter the serum level of vit D is reported to be lower in older children [35], as confirmed by the authors in previous studies [36,37]. In our study, significantly lower levels of vit D were found in children with recurrent wheezing than in either of those with a single episode, or in the control group, only at baseline evaluation.…”
Section: Discussionsupporting
confidence: 89%
“…To analyze platelet function, first, we tested some specific platelet markers from GBC and derivatives (as described in the Methods). It has been shown that platelets do change in size and volume when stimulated [ 24 , 25 ]. We found no significant changes in MPV, PDW, P-LCR, or other platelet markers between the study groups.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL7 and sP-selectin, alone and combined, are statistically significant to discriminate sepsis and bacterial infections from other diseases [17]. In pediatric patients in whom an acute infectious event is suspected, CXCL4 and serotonin levels are not indicative in discriminating the etiology of the event in progress; CXCL4 has a role during the viral response, and its elevation in the blood stream is not significant in patients with sepsis or bacterial infections [18]. However, the values are not yet standardized in the pediatric population, and more studies are necessary to confirm normal values in healthy children and in different clinical conditions, i.e., chronic inflammation, trauma, and acute infection [19].…”
Section: Platelet Indicesmentioning
confidence: 99%